2022
DOI: 10.1002/admi.202201140
|View full text |Cite
|
Sign up to set email alerts
|

Core‐Shell Se‐Doped TiO2@Carbon Nanotubes for High‐Performance Sodium‐Ion Batteries

Abstract: Titanium dioxide (TiO2) has been considered as a promising anode material for sodium‐ion batteries (SIBs), because of its abundance, safety and eco‐friendliness. However, the inferior electronic conductivity and low sodium ion diffusion rate of TiO2 hinder its improvement of electrochemical performance. To overcome these drawbacks, herein, core‐shell Se‐doped TiO2@carbon nanotubes (denoted as Se‐TiO2@CNTs) are successfully designed and fabricated, in which the TiO2 nanoparticle aggregated shells are conformall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The kinetics and mechanism of lithium storage in the Sb 2 O 3 /rGO electrode were further analyzed by electrochemical impedance spectroscopy (EIS). Figure c shows the EIS spectra of Sb 2 O 3 /rGO-100, Sb 2 O 3 /rGO-200, and Sb 2 O 3 before cycling, where the diameter of the semicircle in the high-frequency region represents the charge transfer resistances R ct , while the sloping line in the low-frequency region corresponds to the ions diffusion ability . Apparently, Sb 2 O 3 /rGO-100 (133.51 Ω) shows a smaller R ct than Sb 2 O 3 /rGO-200 (157.94 Ω) and Sb 2 O 3 (218.59 Ω), which is attributed to the porous network structure of the Sb 2 O 3 /rGO-100 composite providing a faster transfer channel for electron.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics and mechanism of lithium storage in the Sb 2 O 3 /rGO electrode were further analyzed by electrochemical impedance spectroscopy (EIS). Figure c shows the EIS spectra of Sb 2 O 3 /rGO-100, Sb 2 O 3 /rGO-200, and Sb 2 O 3 before cycling, where the diameter of the semicircle in the high-frequency region represents the charge transfer resistances R ct , while the sloping line in the low-frequency region corresponds to the ions diffusion ability . Apparently, Sb 2 O 3 /rGO-100 (133.51 Ω) shows a smaller R ct than Sb 2 O 3 /rGO-200 (157.94 Ω) and Sb 2 O 3 (218.59 Ω), which is attributed to the porous network structure of the Sb 2 O 3 /rGO-100 composite providing a faster transfer channel for electron.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, many efforts have been made to develop high‐performance anode materials, including intercalation‐type hard carbon/oxides (e. g., TiO 2 ), [8–10] hybrid‐type metal chalcogenides (e. g., MoS 2 ), [11] conversion‐type metal oxides/chalcogenides (e. g., CoSe 2 ), [12] alloy‐type metals/metal oxides (e. g., Sb, SnO 2 ) [9,13,14] . Among these candidates, MoS 2 and metallic Sb have been identified as promising anode materials for SIBs [9,11,13] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the practical capacity of TiO 2 (B) for Na + storage is still not high enough, and its semiconductive characteristic also hinders the rate performance. Some strategies such as heteroatom doping or incorporation of carbon into TiO 2 (B) have been adopted to improve its performance. Yang et al reported the synthesis of N-doped TiO 2 (B) nanorods, which exhibited a higher specific capacity of 224.5 mAh g –1 and enhanced rate capability (110 mAh g –1 at 3.35 A g –1 ) as compared with anatase TiO 2 and undoped TiO 2 (B) . Huo et al prepared nanowire-like TiO 2 (B)/carbon nanocomposites, which also exhibited improved performance as the anode material of SIBs .…”
Section: Introductionmentioning
confidence: 99%